Infringements of Competition Rules: An Analysis of Unethical and Illegal Behaviours of Entrepreneurs in Poland - Hernik, Joanna (Journal of Corporate Responsibility and Leadership, 2018)
Purpose: Certainly, competitiveness and competition are attribut-ed to human nature. But it is no longer certain that this also applies to ethical behaviour and responsibility, although responsible businesses are also those which respect the law. For this reason, many countries established institutions and laws protecting equal opportunities of entrepreneurs on the market. The purpose of this article is to analyse cases of non-compliance with the rules of fair competition, and then to determine characteristics of the analysed cases in terms of a sphere of activity of an entrepreneur, and the nature of violation. In particular, there will be examined agreements restricting competition and abuse of entrepreneur’s dominant position. Finally, trends in changes will be identified. Design/methodology/approach: A critical analysis of literature, an analysis of legal acts, and an analysis of violations of law reports were used. Empirical data about violations were taken from reports of the Office of Competition and Consumer Protec-tion, which aim is to protect competition in Poland. Cases from 2012 and 2015 were taken for analysis (54 in total). Findings: All the cases from 2012 and 2015 were analysed. Regarding non-competition agreements, only companies were accused (no public institutions). Within three years, the nature of violation changed from imposition of prices to fixing behaviours of companies in tenders. In case of abuse of entrepreneur’s dominant position, the main group of accused organisations were self -governments (communes). Again, within three years the nature of violation changed from imposition of unfavourable contracts to burden of unfair fees. Because of the large number of factors influencing behaviour of entrepre-neurs on the market it is impossible to determine rationales of the change, so for that reason only their nature is described. Research and practical limitations/implications: Information about violations of law was taken from reports of the Office of Competition and Consumer Protection, and due to the large material range, cases from years 2012 and 2015 were selected for analysis. For more accurate results, a broader scope of research should be included, so this work can be a base for further research. Originality/value: The article discusses spheres of business and types of actions that are not in line with fair competition practices. Paper type: theoretical with case analysis.